2010
DOI: 10.1128/iai.01134-09
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa Cytotoxin ExoU Is Injected into Phagocytic Cells during Acute Pneumonia

Abstract: ExoU, a cytotoxin translocated into host cells via the type III secretion system of Pseudomonas aeruginosa, is associated with increased mortality and disease severity. We previously showed that impairment of recruited phagocytic cells allowed survival of ExoU-secreting P. aeruginosa in the lung. Here we analyzed types of cells injected with ExoU in vivo using translational fusions of ExoU with a ␤-lactamase reporter (ExoU-Bla). Cells injected with ExoU-Bla were detectable in vitro but not in vivo, presumably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
110
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(112 citation statements)
references
References 41 publications
1
110
1
Order By: Relevance
“…Therefore, we set out to identify host cells that receive T4SS-translocated effectors during infection with L. pneumophila. BlaM reporter systems have been used during in vivo infection with Yersinia pseudotuberculosis (67,68), Yersinia pestis (69,70), Yersinia enterocolitica (71), Salmonella enterica serovar Typhimurium (72,73), and Pseudomonas aeruginosa (74,75) to detect the translocation of effectors into host cells by the type III and type IV secretion systems. We demonstrate in this study that by using ␤-lactamase (BlaM) translationally fused to the T4SS-translocated effector protein RalF, we can successfully track injection by the T4SS into host cells during both in vitro and in vivo infection, and we describe the first use of this BlaM reporter during in vivo pulmonary infection with L. pneumophila.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we set out to identify host cells that receive T4SS-translocated effectors during infection with L. pneumophila. BlaM reporter systems have been used during in vivo infection with Yersinia pseudotuberculosis (67,68), Yersinia pestis (69,70), Yersinia enterocolitica (71), Salmonella enterica serovar Typhimurium (72,73), and Pseudomonas aeruginosa (74,75) to detect the translocation of effectors into host cells by the type III and type IV secretion systems. We demonstrate in this study that by using ␤-lactamase (BlaM) translationally fused to the T4SS-translocated effector protein RalF, we can successfully track injection by the T4SS into host cells during both in vitro and in vivo infection, and we describe the first use of this BlaM reporter during in vivo pulmonary infection with L. pneumophila.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting strain MDM1542 (Table 1) exhibits Gm r that is dependent on induction of T3SS and lost in the presence of T3SS inhibitors. A single copy of a gene encoding full-length ExoS (lacking adenosine diphosphate ribosyltransferase [ADPRT] activity due to two mutations, E379A/E381A) fused to TEM1 ␤-lactamase (BLA) on miniCTX1 (28) was constructed essentially as described previously for miniCTXexoU-BLA (29). First, the stop codon was removed from exoS using the primers exoSdeltastopF and exoSdeltastopR (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Second, we had previously demonstrated that PrtR is required for the expression of P. aeruginosa type III secretion system (T3SS) genes by repressing the expression of PtrB, a specific inhibitor of the T3SS (12). The T3SS plays an important role in the killing of neutrophils and is thus essential for survival and replication of the bacteria within the host environments (13)(14)(15).…”
mentioning
confidence: 99%